Effect of Giving Mahkota Dewa Fruits (Phaleria Macrocarpa) Extract to Epithelialization In Incision Wound of White Rats (Rattus Norvegicus) - Idola Perdana Sulistyoning Suharto (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2017)
The research purpose was to analysis effect of giving mahkota dewa fruits (Phaleria macrocarpa) extract to epithelialization in incision wound of white rats (Rattus norvegicus). The method was randomized posted-only control group design. There were 30 male rats (Rattus norvegicus) grouped on control and treatment group. Control group divided into three groups (KK1, KK2, KK3) and also treatment group divided into three groups (KP1, KP2, KP3). Control group just given CMC 1% peroral without mahkota dewa fruits extract, the treatment group given mahkota dewa fruits extract 22.5 mg/kg body weight. The data was analyzed by Kruskall Wallis. Based on Kruskall Wallis test, obtained result that there was a significant difference (p<0.05) epithelialization variable with p value p = 0.000 between control and treatment group. And based on One-way Anova test, obtained result that there was a significant difference (p<0.05) with p value p =0.000 between control and treatment group. The conclusion of this research was giving mahkota dewa fruits (Phaleria macrocarpa) extract can increase epithelialization in incision wound of white rats (Rattus norvegicus). Keywords : Mahkota Dewa Fruits (Phaleria Macrocarpa) Extract, Epithelialization, Incision Wound